Identification of biomarker panels as predictors of severity in coronary artery disease. Issue 3 (31st December 2020) - Ben Braiek, Assia; Chahed, Hinda; Dumont, Florent; Abdelhak, Fodha; Hichem, Denguir; Gamra, Habib; Baudin, Bruno
Abstract: Matrix metalloproteinases (MMPs) are implicated in atherosclerotic plaque rupture and recondition. Specific tissue inhibitors (TIMPs) control MMP functions. Both MMPs and TIMPs are potential biomarkers of plaque instability. Elevated Apo‐CII and CIII and Apo‐E levels are recognized as cardiovascular disease risk factors. We aimed to establish the best blood biomarker panel to evaluate the coronary artery disease (CAD) severity. Plasma levels of MMP‐3 and MMP‐9, TIMP‐1 and TIMP‐2, Apo‐CII, Apo‐CIII and Apo‐E were measured in 472 patients with CAD evaluated by coronary angiography and electrocardiography, and in 285 healthy controls. MMP‐3 and MMP‐9 plasma levels in CAD patients were significantly increased ( P < 0.001) compared to controls (3.54‐ and 3.81‐fold, respectively). Furthermore, these increments are modulated by CAD severity as well as for Apo‐CII and Apo‐CIII levels ( P < 0.001). TIMPs levels were decreased in CAD versus controls ( P < 0.001) and in inverse correlation to MMPs. Standard ROC curve approach showed the importance of panels of biomarkers, including MMP‐3, MMP‐9, TIMP‐1, TIMP‐2, Apo‐CII and Apo‐CIII, for disease aggravation diagnosis. A high area under curve (AUC) value (0.995) was reached for the association of MMP‐9, TIMP‐2 and Apo‐CIII. The unbalance between MMPs and TIMPs in vascular wall and dyslipidaemia creates favourable conditions for plaque disruption. Our study suggests that the combination of MMP‐9, TIMP‐2 and Apo‐CIII values ('CAD aggravation panel') characterizes the severity of CAD, that is electrophysiological state, number of involved vessels, stent disposal and type of stent.